WAYS TO CREATE A POSITIVE ENVIRONMENT FOR FOREIGN LANGUAGE TEACHING - Rustamova, Shahnoza; Turg`unova Fazilat Rustam qizi, (Журнал иностранных языков и лингвистики, 2023)
Our article discusses effective methods of creating an emotionally positive atmosphere in foreign language teaching, mainly as a factor determining the success of the learning process.